2008
DOI: 10.1074/jbc.m710157200
|View full text |Cite
|
Sign up to set email alerts
|

Box 2 Region of the Oncostatin M Receptor Determines Specificity for Recruitment of Janus Kinases and STAT5 Activation

Abstract: Human and murine oncostatin M (OSM) induce their bioactivities through a heterodimeric receptor complex consisting of gp130 and the OSM receptor (OSMR), which initiates a signaling pathway involving Janus kinases (JAKs) and transcription factors of the signal transducers and activators of transcription (STAT) family. In contrast to the signal transducing receptor subunit gp130, the OSMR allows strong activation of STAT5B. The underlying molecular mechanism, however, remained unclear. Here we demonstrate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 52 publications
4
29
0
Order By: Relevance
“…4B, upper panel). Previous studies have shown that STAT5 can be directly activated by JAK2 after cytokine stimulation (30,32). To corroborate our results, we treated HDFs with AG490, an inhibitor with higher affinity to JAK2 than to other JAK family members.…”
Section: Osm-induced Production Of Ccl1 But Not Ccl8 Is Negatively supporting
confidence: 84%
See 2 more Smart Citations
“…4B, upper panel). Previous studies have shown that STAT5 can be directly activated by JAK2 after cytokine stimulation (30,32). To corroborate our results, we treated HDFs with AG490, an inhibitor with higher affinity to JAK2 than to other JAK family members.…”
Section: Osm-induced Production Of Ccl1 But Not Ccl8 Is Negatively supporting
confidence: 84%
“…Previous work has highlighted the importance of JAK2 for the STAT5 tyrosine phosphorylation (30,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, our group showed that JAK-2 significantly contributes to OSM-induced STAT-5 activation (44). Thus, the JAK-2 inhibitor AG490 was used to compare the impact of STAT-5 with the impact of MAPK on CCL13 expression in normal SFs.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, tyrosine residues at positions 917 (Tyr-917) and 945 (Tyr-945) serve as docking sites for STAT3 in OSM signaling (21). To analyze the role of Tyr-917 and Tyr-945 in STAT3 activation by a receptor complex composed of OSMR␤ and IL-31R␣, we created single and double mutants of OSMR␤ in which the tyrosines were substituted by phenylalanine (Y917F, Y945F, and Y917F/Y945F).…”
Section: Osmr␤ Expression Is a Prerequisite For Functional Il-31mentioning
confidence: 99%